Spin-Vibronic Control of Intersystem Crossing in Iodine-Substituted Heptamethine Cyanines - Tovtik, Radek; Muchová, Eva; Štacková, Lenka; Slavíček, Petr; Klán, Petr (The Journal of organic chemistry, 2023)
Spin-orbit coupling between electronic states of different multiplicity can be strongly coupled to molecular vibrations, and this interaction is becoming recognized as an important mechanism for controlling the course of photochemical reactions. Here, we show that the involvement of spin-vibronic coupling is essential for understanding the photophysics and photochemistry of heptamethine cyanines (Cy7), bearing iodine as a heavy atom in the C3' position of the chain and/or a 3H-indolium core, as potential triplet sensitizers and singlet oxygen producers in methanol and aqueous solutions. The sensitization efficiency was found to be an order of magnitude higher for the chain-substituted than the 3H-indolium core-substituted derivatives. Our ab initio calculations demonstrate that while all optimal structures of Cy7 are characterized by negligible spin-orbit coupling (tenths of cm-1) with no dependence on the position of the substituent, molecular vibrations lead to its significant increase (tens of cm-1 for the chain-substituted cyanines), which allowed us to interpret the observed position dependence.